2022
DOI: 10.1111/jonm.13550
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the fear of COVID‐19 and professional quality of life among nurses: A multicultural study

Abstract: Aim To determine the factors that influence nurses' fear of COVID‐19 and professional quality of life as well as their attitudes towards COVID‐19 in four different countries. Background The emergence of COVID‐19 has affected the psychological and professional quality of life of the frontline health care workers, especially nurses. Design An online cross‐sectional multicultural study. Methods A total of 1071 nurses from Turkey, Brazil, Spain and Italy were selected by convenience sampling. All participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 54 publications
8
25
0
Order By: Relevance
“…Our results are generally in line with the majority of studies which demonstrated a significant negative impact of FCV-19 on mental health outcomes, work outcomes, quality of life, and job performance in HCWs [ 8 , 11 , 32 , 40 , 41 , 42 , 43 ]. However, the comparison of our results with those of the above studies should be considered with caution given that in many of them, FCV-19 was measured through ad hoc questions and not with validated tools.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results are generally in line with the majority of studies which demonstrated a significant negative impact of FCV-19 on mental health outcomes, work outcomes, quality of life, and job performance in HCWs [ 8 , 11 , 32 , 40 , 41 , 42 , 43 ]. However, the comparison of our results with those of the above studies should be considered with caution given that in many of them, FCV-19 was measured through ad hoc questions and not with validated tools.…”
Section: Discussionsupporting
confidence: 91%
“…According to a recent meta-review [ 10 ], our results conform to the rates of BO reported by HCWs worldwide during the third wave [ 35 ]. Additionally, these results converge to those of reports indicating low to moderate levels of STS in HCWs during the pandemic [ 32 , 36 , 37 ]. We found only two studies that examined ProQOL and its dimensions (CS, BO, STS) in MHWs during COVID-19 [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations